2000
DOI: 10.2307/1593096
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Subtype Strains of the Arkansas Serotype of Infectious Bronchitis Virus in Delmarva Broiler Chickens

Abstract: Infectious bronchitis virus (IBV) field isolates of the Arkansas (Ark) serotype were identified by reverse transcription-polymerase chain reaction (RT-PCR) as the most common serotype isolated from 1993 to 1997. These isolates were recovered from broiler flocks with respiratory disease raised on the Delmarva peninsula in spite of Ark vaccination in the region. For the purposes of investigating this apparently paradoxical finding, five RT-PCR Ark-positive field isolates recovered in 1995 and 1996 were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
48
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 21 publications
3
48
0
Order By: Relevance
“…In contrast, Nix et al (2000) reported an increasing frequency of Arkansas (Ark)-type IBV isolations in the Delmarva Peninsula (northeastern United States) between 1992 and 1997 in spite of use of ArkDPI-derived vaccines. In the southeastern United States, over one-half of IBV isolates obtained between 1997 and 2002 were ArkDPI-like (Toro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Nix et al (2000) reported an increasing frequency of Arkansas (Ark)-type IBV isolations in the Delmarva Peninsula (northeastern United States) between 1992 and 1997 in spite of use of ArkDPI-derived vaccines. In the southeastern United States, over one-half of IBV isolates obtained between 1997 and 2002 were ArkDPI-like (Toro et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…At least four different commercial Ark-serotype vaccines derived from this attenuated stock are used in the United States. Two different commercial Ark vaccines, as well as the attenuated ArkDPI seed stock distributed to vaccine companies, and the original unattenuated ArkDPI isolate, have been shown to contain a minor subpopulation similar to an Ark subtype isolated from broilers in the Delmarva Peninsula (Nix et al, 2000). This minor subpopulation was identified by restriction fragment length polymorphism (RFLP) analysis of the S1 gene, real-time polymerase chain reaction (RT-PCR) using primers specific for the subpopulation, and sequencing of the RT-PCR product, but the sequence of the entire S1 gene of the putative subpopulation was not determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective control of infectious bronchitis virus (IBV) has been distinctively difficult because of genetic diversity and continuing evolution of the causal coronavirus (Toro et al, 2012b). In the United States, Arkansas (Ark) type strains have been the most frequently identified type of IBV ranging from 23% to 65% of total isolations per year (Nix et al, 2000;Jackwood et al, 2005;Toro et al, 2006) in spite of Ark serotype vaccination. Other IBV serotypes determined to be widespread in the United States include the Connecticut (Conn), DE072, Massachusetts (Mass) and Georgia serotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Various serological types of live or inactivated vaccines have been available for control of IBV infections in Japan. Vaccines have generally been effective in controlling clinical disease associated with IBV infections, but new variants may continue to emerge and cause clinical disease and production problems in vaccinated flocks [8,18]. Some studies [7,10] have reported frequent isolation of isolates related to vaccine strains from diseased flocks in the field, and reversion of the virulence of vaccine strains and recombination has been suspected.…”
mentioning
confidence: 99%